2018
DOI: 10.1111/sjop.12442
|View full text |Cite
|
Sign up to set email alerts
|

Attachment security, values, and prosocial attitudes

Abstract: The objective of this study was to determine whether individuals with different attachment styles held different prosocial values and attitudes given their different models of self and of others. A sample of 717 university students completed the ECR-S (Experiences in Close Relationships-Spanish) and the PVQ (Portrait Values Questionnaire), and evaluated different prosocial attitudes. The results showed that secure individuals reported higher scores on self-transcendence and in the value self-directions of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 39 publications
3
12
0
Order By: Relevance
“…However, if such a comparison would have revealed a link between RAD symptoms and SBS knowledge, it would still have been impossible to claim that insecure attachment is the core and most speci c issue that children with ASD struggle with, because theory suggests that the average child with any mental health problem will have less SBS knowledge than healthy controls [66]. This way, the current ndings resonate with other studies that failed to nd a link between RAD symptoms and insecure attachment [37] and with a mounting number of scholars argueing that insecure attachment is not the core and speci c issue characterizing attachment disorder symptoms [27,35,36,38].…”
Section: Discussionsupporting
confidence: 66%
“…However, if such a comparison would have revealed a link between RAD symptoms and SBS knowledge, it would still have been impossible to claim that insecure attachment is the core and most speci c issue that children with ASD struggle with, because theory suggests that the average child with any mental health problem will have less SBS knowledge than healthy controls [66]. This way, the current ndings resonate with other studies that failed to nd a link between RAD symptoms and insecure attachment [37] and with a mounting number of scholars argueing that insecure attachment is not the core and speci c issue characterizing attachment disorder symptoms [27,35,36,38].…”
Section: Discussionsupporting
confidence: 66%
“…They have developed positive internal working models which motivates adolescents to collaborate with each other because they believe it is worth it [33]. Such secure attachment may contribute to children's ability to form meaningful peer relationships when they enter school [34]; these relationships may provide increased opportunities to participate in prosocial behaviors, which in turn sustain positive interactions with peers into adolescence, reinforcing children's views of others as good and worthy of care [35]. On the contrary, insecure attached adolescents have negative expectations and hostile attributions about peer behaviors that likely undermines prosocial behavior [36,37].…”
Section: Importance Of Secure Peer Attachment Relationshipsmentioning
confidence: 99%
“…Results suggested that attachment representations might indeed be important to understand this association, but that they act as a moderator and not as a mediator in the ADS-prosocial behavior problems association. ADS and SBS knowledge were not related in this study, which is important in light of the growing discussion on the relevance of attachment theory to understand ADS [24,27,32,33,35]. Adding to the discussion, the current study calls for careful reasoning to a literature that is characterized by a growing demand to discard the connection between attachment theory and the Attachment Disorders diagnoses [62,63].…”
Section: Resultsmentioning
confidence: 77%
“…In all, theory predicts to nd that all children with ADS display ruptured trust in the availability of their primary caregivers, mirrored in insecure attachment representations. In turn, attachment theory assumes that insecure attachment representations are linked with children's decreased prosocial behavior [24]. Theory suggests that decreased prosocial behavior serves a protective function for insecurely attached children: because they anticipate that they cannot rely on others for support they are more motivated to create social distance to avoid further relational pain [25,26].…”
Section: Introductionmentioning
confidence: 99%